ENVIRONMENTAL CONFLICTS IN SAO CARLOS/SP: MAPPING AS A DIAGNOSIS AND SUBSIDY TO PLANNING MUNICIPAL PUBLIC POLICIES - Oliveira, Celso Maran de; Nunes de Sousa, Isabel Cristina [UNESP] (Univ Estado Rio Janeiro, 2021)
Identifying, quantifying, and mapping environmental conflicts contributes to the planning of public policies based on diagnoses from empirical information, focusing on the distribution of disturbances in the environment. In this paper, we analyze the environmental conflicts of a medium-sized Brazilian city, aiming to identify the main environmental problems and guide the planning and environmental management activities. Environmental damages identified in Sao Carlos/SP were quantified, typified, and evaluated based on the literature about the anthropic interventions and environmental fragilities in the study area, through a survey and characterization of the spatial distribution of environment conflicts from Civil Inquiries initiated and conducted by the Sao Paulo State Prosecutor's Office, institutionalized in the period from 2006 to 2016. The primary data collected were organized and analyzed through a predominantly quantitative approach, with exploratory analysis, bibliographic and documentary research, as well as spatialization of conflicts in the Sao Carlos territory. We observed a decrease in the original vegetation cover, environmental degradation due to pollution, and recurrent damage to the wildlife, with a notable concentration of conflicts in the central area of the city.
Keywords: Environmental Law; Institutionalized Conflicts; Environmental Damages; Spatial Analysis; GIS